Expression of multidrug resistance 1 gene in B‐cell lymphomas: association with follicular dendritic cells. Issue 3 (22nd January 2013) - Yagi, Keiko; Yamamoto, Kouhei; Umeda, Shigeaki; Abe, Shinya; Suzuki, Shiho; Onishi, Iichiroh; Kirimura, Susumu; Fukayama, Masashi; Arai, Ayako; Kitagawa, Masanobu; Kurata, Morito
<x xml:space="preserve">Abstract</x> Aims: Multidrug resistance (MDR) in B‐cell lymphomas still constitutes a major obstacle to the effectiveness of chemotherapy even in the anti‐CD20 antibody therapy era. The aim of this study was to investigate the expression of MDR‐associated molecules in reactive lymphadenopathy (RL), follicular lymphoma (FL), and diffuse large B‐cell lymphoma (DLBCL). Methods and results: The expression of mRNA for ABC‐transporter family genes was determined by real‐time RT‐PCR in lymph nodes from RL, FL, and DLBCL cases. MDR1 exhibited significantly stronger expression in RL, FL, and DLBCL than Raji B‐cell lymphoma cells. RL and FL showed significantly higher expression than DLBCL. Immunohistochemically, MDR1 positive cells were localized in the germinal centers of RL and center of the nodular lesions of FL showing associations with CD21 positive follicular dendritic cells (FDCs). Raji cells were co‐cultured with FDC sarcoma‐derived cells and the expression of MDR1 and drug resistance were analyzed. The co‐culture of Raji cells with FDCs induced strong expression of MDR1 and introduced resistance to doxorubicin‐induced apoptosis. Conclusions: These results suggest that FDCs induce MDR1 expression in reactive as well as neoplastic B‐cells. Inhibition of the interaction of FDCs with B‐cells may provide a novel strategy for treating the chemotherapy resistant fraction.